The Robust Impact of Macroeconomic Factors Towards Market Valuation Among Energy Sector Across Countries - SAAD, NORIZA MOHD (The journal of contemporary issues in business and government, 2021)
This paper investigated the significant mean difference in market valuation by companies across countries. Further, it investigated the impact of macroeconomic factors proxies by Gross Domestic Product (GDP growth), Consumer Price Index (CPI), and Interest Rate (IR) towards the energy firms’ market valuation proxy by Tobins’ Q ratio. Secondary data were utilized for an unbalanced panel which consisted of eight countries. A total of 747 listed companies was the sample size that spanned through ten years (from 2010 to 2020). Data were gathered from Bloomberg. The study employed Scheffe method for comparison analysis and multivariate regression for impact analysis that was modelled into ordinary least square, random effect, fixed effect, and random effect robust. The best-fit model was chosen based on the results of the Bruesh Pagan Langragian Multiple (BP-LM) effect besides checking on heterokedasticity problem. The results obtained rectify that there is no multicolinearity issue and no heterokedasticity problem in data analysis. Therefore, the reported findings confirm that there are positive relationships and impact of GDP and CPI on Tobins’Q as well as a significant inverse relationship with interest rate factor across the countries.